KEMAMPUAN MENULIS PUISI SISWA KELAS X SMA NEGERI 1 BANDAR SRIBHAWONO LAMPUNG TIMUR TAHUN PELAJARAN 2011/2012 - chelistya eryesma anwar; edy suyanto; mulyanto widodo (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2013)
The problem in this research was the ability of writing poetry of the students. The objective of this research was to describe the ability of writing poetry of the students class X of SMA Negri 1 Bandar Sribowono Lampung Timur academic year of 2011/2012.The method that used in this research was descriptive method. The population in this research was the students class X of SMA Negri 1 Bandar Sribawono Lampung Timur academic year of 2011/2012 that consists of 278 students and laid in nine classes. The sample was taken by using proportional cluster random sampling technique. Each class was taken 10% to be the sample then got 27 students as the sample. The primary technique that was used to collect the data was test of writing poetry by themes; sociality, patriotism, social critic, and togetherness. The reason of the researcher decided four themes was to gather the students in writing poetry.The result of the research showed that the average of students’ ability in writing poetry was good “enough” that was, gaining the percentage in average 67.62%. the average of ability in each aspect was (1) expressing the themes was categorized good “enough” by average score 71.48%, (3) choosing the dictions was categorized  good “enough”  by average score 65.55%, (4) expressing imagination  was categorized good “enough” by average score 65.18%, (5) the using of figure of a speech was less “weak” by average score 61.85%.The average scores showed that the highest skill that reached by the students class X in writing poetry that was on the aspect of explicit message, whereas in the low ability that reached by the students was on the using the figure of speech. Thereby, it can be concluded that that the level of students’ ability in writing poetry is categorized good “enough”. Key words: the ability of writing poetry of the students class X of SMA Negri 1 Bandar Sribawono Lampung Timur.